An Analysis of Arabic Esl Students’ Past Participle Error Found in STAI Ali Bin Abi Thalib Surabaya - Kadiatmaja, Agung Pranoto (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
This research examines past participle errors in students' writing term papers to identify their difficulties. The error analysis is part of an investigation into the English language learning process. The purpose of this research is to identify the types of error analysis and the most dominant types of error analysis in the use of past participles. The qualitative research was carried out to investigate errors in second language acquisition. The research concentrates on qualitative research, collecting empirical data from students' writing through document analysis. The method is used to collect accurate data. The research focuses on eleven undergraduates from the Arabic Department at STAI Ali bin Abi Thalib Surabaya. To obtain the results of this error analysis, the researcher investigates further using surface strategy taxonomy. It is restricted to the students' past participle error, which consists of four error types: omission, addition, misformation, and misordering. At last, after identifying all of the data and analyzing the research findings, it can be summarized that the types of past participle errors produced by the students are: (1) omission, which occurred 10 times, or 66,67% of all; (2) addition, which occurred 4 times, or 26,67% of all; (3) misformation, which occurred once, or 6,66% of all; and (4) misordering error, which did not occur. According to the research findings, the most dominant type of past participle error is omission. Error Analysis, Writing, Past Participle.